2011
DOI: 10.1364/oe.19.014508
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing speckle contrast for HiLo microscopy optimization

Abstract: HiLo microscopy is a recently developed technique that provides both optical sectioning and fast imaging with a simple implementation and at a very low cost. The methodology combines widefield and speckled illumination images to obtain one optically sectioned image. Hence, the characteristics of such speckle illumination ultimately determine the quality of HiLo images and the overall performance of the method. In this work, we study how speckle contrast influence local variations of fluorescence intensity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…As expected from other work in the microscopic domain 18 , it was found that the speckle pattern for the structured illumination image needed to be coarser when imaging thicker samples (more than ~100 μm thick). In the ideal case, the transverse size of an imaged speckle grain was determined by the illumination NA 14,17 .…”
Section: Figure 1: Comparison Of Optical Sectioning Strengthsupporting
confidence: 76%
See 3 more Smart Citations
“…As expected from other work in the microscopic domain 18 , it was found that the speckle pattern for the structured illumination image needed to be coarser when imaging thicker samples (more than ~100 μm thick). In the ideal case, the transverse size of an imaged speckle grain was determined by the illumination NA 14,17 .…”
Section: Figure 1: Comparison Of Optical Sectioning Strengthsupporting
confidence: 76%
“…We have shown here a fast widefield optical sectioning method for the Mesolens using widefield camera image, no fine detail is lost 18 . This method presents a significant speed advantage over CLSM at comparable sectioning strength of ~5μm, being 30 times faster in raw data acquisition.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Bottom: Deviations from uniformity in the images on top. This artifact in HiLo is a known consequence of statistical fluctuations in the total illumination dose, and is not corrected by increasing the exposure time 41 . Hadamard and stripe SIM microscopies avoided this artifact by providing illumination whose time-average intensity was precisely the same at all sample points.…”
Section: Discussionmentioning
confidence: 99%